Uveitis: Molecular Pathogenesis and Emerging Therapies - Egwuagu, Charles E.; Alhakeem, Sahar A.; Mbanefo, Evaristus C. (Frontiers in Immunology, 2021)
Vision and survival are intricately linked, and existential value of the eye led to early advances in understanding of ocular inflammatory diseases and their management. Thus, investigations of the pathogenesis of ocular diseases such as sympathetic ophthalmia and endophthalmitis phacoanaphylactica played a foundational and important role in our current understanding of how the immune system distinguishes self from non-self. These early studies of intraocular inflammatory diseases or uveitis accelerated the rejection of Ehrlich’s theory of “horror autotoxicus” and eventual acceptance of the concept of immune tolerance and acknowledgement of existence of autoimmune diseases. The unique anatomic features of the eye and its sequestration from peripheral immune system provide a framework or organ system for understanding basic immunological principles and evaluating the efficacy or safety of biologics and emerging immunotherapies. Here, we have reviewed studies on the molecular pathogenesis of uveitis over the past 3 decades. These studies have advanced our understanding of molecular mechanisms that underlie susceptibility or resistance to organ-specific autoimmune diseases and the development of targeted cell-based immunotherapies for the treatment of uveitis and CNS autoimmune diseases.